CONVERGENCE OR DIVERGENCE: THE ISSUE BETWEEN ETHICS AND POLITICS - Pineda Jiménez, Jacinto (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Those This document seeks to contribute to the they debate the paper of the the sober of the ethics of the or of the one in the political life between moral of the lost one of widespread of that of the trust in the political institutions. He/she leaves them of the they debate the politics he/she enters in the ethics of and the and from this incessant discussion to find arguments that facilitate to understand the crisis of the trust that affects the democracies. The The mark reflexive orientador is determined by the contributions of the discursive one of ethics of that of Habermas the one of and of the as of the authors Adela Cortina, Jhon Rawls and Victoria Camps those that assume a convergent relationship enter in the ethics the politics of and.